Effect of the calcinations temperatures of phosphate washing waste on the structural and mechanical properties of geopolymeric mortar. (10th October 2018) - Dabbebi, R.; Barroso de Aguiar, J.L.; Camões, A.; Samet, B.; Baklouti, S.
Highlights: Phosphate washing waste is one of phosphate sub product. The calcined phosphate washing waste was used as geopolymer precursors. The performance and the formed phases after alkali activation depend with calcination temperature. Abstract: The phosphate industry is facing serious environmental problems. This issue is caused by the waste after the extraction of the phosphate ore. The waste termed as phosphate washing waste (PWW) was filtered and dried at 105 °C for 24 h to remove the water. The dried PWW was milled, sieved in a 100 µm sieve and characterized by X-ray fluorescence (XRF). The resulting waste was calcined at 600, 700 and 800 °C, the calcined and uncalcined waste were investigated by X-ray powder diffraction (DRX), Fourier transform infrared (FTIR), simultaneous differential thermal and thermogravimetric analyses (DSC-TG) and scanning electron microscope (SEM). The PWW was activated with sodium hydroxide (NaOH) and sodium silicate to produce geopolymeric materials. It was found that the calcination temperature and the extra water added to the mixture to assure the good workability play an important role on the development of the system's workability and compressive strength.